Tapping the untapped potential: India-Ireland trade & investment opportunities post-Brexit - Nisha Taneja; Isha Dayal; Tanu M. Goyal; Sanya Dua (Indian Council for Research on International Economic Relations (ICRIER), 2022)
Recent events, particularly Brexit, have propelled India to diversify its trade and investment markets in the European Union (EU). Within the EU, India has trade and investment synergy with Ireland. The paper explores business opportunities between India and Ireland, by analysing their bilateral trade in goods and services, and foreign direct investments. The paper analyses disaggregated bilateral trade data and uses the trade possibilities approach to estimate India's goods trade with Ireland and India's potential exports to Ireland. It is found that India has an untapped export potential of US19 billion in the Irish market with the top 50 items accounting for 71 percent of the total potential. Exports of pharmaceuticals, organic chemicals and surgical goods dominate India's goods exports to Ireland, with there being potential to enhance such trade. Further, services are the largest component of India-Ireland trade and there is potential for increasing India's services export to Ireland, especially in business services, education, tourism, and medical services. Foreign direct investments from India to Ireland are predominantly in the manufacturing sector, particularly in manufacturing of medical and pharmaceutical items while FDIs from Ireland to India have been rising especially in business services, with potential to strengthen investment ties further through investments and collaborations in emerging technologies. The paper suggests that further boost to bilateral ties can come from the opportunities that are likely to be unleashed from the forthcoming India-EU free trade agreement and an India-EU bilateral trade and investment agreement.
Keywords: C82; F13; F23; 330; India - Ireland trade; export potential; services trade; foreign direct investment; technology collaborations